Analysis of Urban Growth and Sprawl from Remote Sensing Data - Bhatta, Basudeb; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book provides a comprehensive discussion on urban growth and sprawl, and how they can be analyzed using remote sensing imageries. It compiles the views of numerous researchers which help in understanding urban growth and sprawl; their patterns, process, causes, consequences, and countermeasures; how remote sensing data and geographic information system techniques can be used in mapping, monitoring, measuring, analyzing, and simulating the urban growth and sprawl; and the merits and demerits of current methods and models. Scientists and researchers engaged in urban geographic research will benefit greatly from this book, especially when using remote sensing imageries. Post graduate students of urban geography or urban/regional planning may refer to this book for additional information. This book should also assist academicians when preparing lecture notes and delivering lectures. Professionals in related fields in industry will appreciate the methods and models discussed as well as the many citations.
Urban Growth and Sprawl -- Causes and Consequences of Urban Growth and Sprawl -- Towards Sustainable Development and Smart Growth -- Remote Sensing, GIS, and Urban Analysis -- Mapping and Monitoring Urban Growth -- Measurement and Analysis of Urban Growth -- Modelling and Simulation of Urban Growth -- Limitations of Urban Growth Analysis.
Keywords: Geography; Mathematical geography; Information systems; Information Systems; Environmental management; Earth Sciences; Computer Applications in Earth Sciences; Environmental Management; Information Systems Applications (incl.Internet).; Management of Computing and Information Systems